2012
DOI: 10.1177/0748233712463780
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl cysteine and erdosteine treatment in acetaminophen-induced liver damage

Abstract: The present study demonstrated that, in the prevention of liver damage induced by acetaminophen intoxication, an early treatment with a single dose of erdosteine was beneficial instead of NAC administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…We were therefore unable to compare our results with those of previous studies. However, in an experimental rat study of paracetamolinduced hepatotoxicity, rats treated with paracetamol were reported to have higher TOS levels and lower TAS levels than the controls (14). Additionally, TOS levels have been shown to increase in rats treated with methotrexate, while TAS levels remained unchanged (13).…”
Section: Histopathological Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We were therefore unable to compare our results with those of previous studies. However, in an experimental rat study of paracetamolinduced hepatotoxicity, rats treated with paracetamol were reported to have higher TOS levels and lower TAS levels than the controls (14). Additionally, TOS levels have been shown to increase in rats treated with methotrexate, while TAS levels remained unchanged (13).…”
Section: Histopathological Assessmentmentioning
confidence: 99%
“…It has been reported that oxidative stress is the common pathophysiological pathway of most types of intoxications. The role of increased oxidative stress has been demonstrated in experimental organophosphate, paracetamol, and methotrexate models (12)(13)(14). Recent in vitro and in vivo studies have suggested that oxidative stress is probably responsible for α-amanitininduced hepatotoxicity in studies (7,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Erdosteine also has an antiinflammatory effect which is mediated through the inhibition of LPS-induced NF-kB activation 4 . The hepatoprotective effects of erdosteine against acetaminophen-induced liver damage, cyclosporine-A-induced hepatotoxicity, experimental biliary obstruction, cisplatininduced hepatic oxidant injury, doxorubicininduced hepatotoxicity, and vancomycininduced oxidative stress in the rat liver have been shown in previous studies [5][6][7][8][9][10][11] . Erdosteine has beneficial effects on ischemia-reperfusion injury in various organs including lung, brain, kidney, intestines, ovaries, and spinal cord [12][13][14][15][16][17] .…”
mentioning
confidence: 69%
“…Based on these concepts, we found that apoptotic hepatocytes were significantly increased in the liver of rats after acetaminophen treatment and the hepatocyte apoptosis was significantly reduced by both curcumin and N-acetylcysteine treatment as detected by quantitative analysis of the immunohistochemical study of p53 antigen. A recent study showed that curcumin exerts a potent anti-apoptotic effect by decreasing the expression of pro-apoptotic genes (Bax, caspase-3) and increasing the expression of anti-apoptotic genes (Bcl-XL) [42]. NAC attenuates lipopolysaccharide induced apoptotic liver injury via its strong ROS scavenging and anti-apoptotic effects [46].…”
Section: Discussionmentioning
confidence: 99%
“…In this study the oxidative damage caused by acetaminophen overdose was significantly attenuated by administrating curcumin and N-acetylcysteine. The most accepted explanation for the protective actions of N-acetylcysteine is that it serves as a source of L-cysteine for GSH synthesis and, hence, it can help the detoxification of NAPQI before this reactive metabolite can initiate hepatic injury [41,42] and acts as a scavenger of ROS that it supports mitochondrial energy metabolism [43]. Likewise to N-acetylcysteine, curcumin could save against free radical mediated oxidative stress by scavenging for free radicals that restricts lipid peroxidation incorporated in membrane damage.…”
Section: Discussionmentioning
confidence: 99%